Prealbumin in the diagnosis of bronchopulmonary carcinoid tumours. Issue 7 (July 1991) - Suresh, U R; Wilkes, S; Hasleton, P S
Abstract : The reliability of prealbumin as a diagnostic marker was studied in 60 cases of bronchopulmonary carcinoid tumours. There were differences in the incidence of positivity between typical and atypical carcinoids (well differentiated neuroendocrine carcinomas). Seventy five per cent of the carcinoid tumours were positive for prealbumin; (86.7% typical and 63.3% atypical carcinoids). In 15 cases, which were Grimelius negative, 10 were prealbumin positive. Only 8.3% carcinoids were negative with both prealbumin and Grimelius stains. Ten squamous, 10 adeno- and 10 small cell carcinomas showed only occasional scattered prealbumin positive cells. It is concluded that prealbumin is a useful marker for bronchopulmonary carcinoid tumours. It is cheap, readily available, and should be considered part of routine diagnostic procedures for the diagnosis of carcinoid tumours.